Investigation of the effects of tripropylene glycol addition to diesel fuel on combustion and exhaust emissions at an isolated diesel engine - Hazar, Hanbey (Pergamon-Elsevier Science Ltd, 2017)
Low emission in diesel engines increases the importance of low fuel consumption and high efficiency. In this experimental study, the parts forming the combustion chamber were coated with ceramic materials, which had low thermal conductivity and resistance to high operating temperature, in order to reduce the loss energy and harmful emissions in a diesel engine. This study was conducted in 3 stages. In the first stage, cylinder liner and the valves were coated by using boronizing method. In the second stage, piston surface was coated by using plasma spray method. In the third stage, tripropylene glycol + diesel mixtures (added as 2%, 4%, and 6% by volume) were used in coated (COE) and uncoated (STE) engines. The results determined that in coated engine, carbon monoxide (CO), hydrocarbon (HC), smoke emissions and brake specific fuel consumption (BSFC) values of diesel fuel and tripropylene glycol + diesel mixtures decreased; whereas, nitrogen oxide (NO),), exhaust gas temperature (EGT) and brake thermal efficiency increased. (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: Diesel engine; Thermal barrier coating (TBC); Tripropylene glycol; Exhaust emissions; Performance